The Laboratory at Hand: Plastic Sorting Made Easy: A next‐generation mobile near‐infrared spectroscopy solution. Issue 5 (6th October 2020) - Schmidt, Felix; Christiansen, Nicole; Lovrincic, Robert
Abstract: Sorting plastics according to their chemical composition is a crucial step in the recycling process, turning mixed plastics waste into a high‐value resource. Near‐infrared spectroscopy (NIRS) is an established method for plastics classification. Evolutionary progress in miniaturization of optical components has enabled the development of hand‐held spectrometers. Cloud‐based computing and centralized databases provide practically unlimited computing power for classification algorithms and enormous spectral databases. Here we discuss the basics of hand‐held NIRS and the essentials of the corresponding data analysis with a focus on plastics sorting.